Route to high-energy density polymeric nitrogen t-N via He−N compounds - Yinwei Li (Nature Portfolio, 2018)
Polymeric nitrogen has yet to be recovered to ambient conditions, precluding its practical application as high-energy density material. Here, the authors highlight a possible route to the formation of a tetragonal polymeric nitrogen via helium-nitrogen compounds at high pressures.